The evolving role of paramedics - a NICE problem to have? - Eaton, G; Mahtani, K; Catterall, M (SAGE Publications, 2018)
This short essay supports the growing role of paramedics in the clinical and academic workforce. We present a commentary of recent draft consultations by the National Institute for Health and Care Excellence in England that set out how the role of paramedics may be evolving to assist with the changing demands on the clinical workforce. Using these consultations as a basis, we extend their recommendations and suggest that the profession should also lead the academically driven evaluation of these new roles.